Burn coverage more important than patchiness for desert predator communities - Emma A.M. Geelen; Daniel F. Bohórquez Fandiño; Tim S. Doherty (Journal of Arid Environments, 2026)

A Tale of Two Tails: Untangling the Phylogeography and Demographic History of Extant Species of Mulgara ( Dasycercus spp.) in the Australian Arid Zone - Aline Gibson Vega; Brenton von Takach; Linette Umbrello; Dympna Cullen; Mark Cowan; Helen Crisp; Chris Dickman; Tim Doherty; William La Marca; Jenny Molyneux; Colleen Sims; Peter B. S. Spencer; et al. (Journal of Biogeography, 2025)
Aim Australia's arid and semi‐arid zones cover about 70% of the continent, yet our understanding of the biogeography of these diverse and expansive landscapes remains limited. Mulgara ( Dasycercus spp.; Marsupialia: Dasyuridae), a widely distributed mammal taxon, offers an opportunity to explore patterns of the population structure across the region, previously hampered by taxonomic confusion surrounding extant species. Here, we aimed to (1) clarify the current distribution of extant Dasycercus lineages, (2) describe the population genomic structure of the widespread brush‐tailed mulgara, and (3) determine whether observed patterns of population genomic structure in brush‐tailed mulgara are consistent with biogeographic breaks. Location Arid and semi‐arid regions of Australia. Taxon Two species are extant; the brush‐tailed mulgara ( D. blythi ) and the crest‐tailed mulgara ( D. hillieri , previously D. cristicauda ). Methods We sampled individuals from contemporary and museum tissue collections, obtaining next‐generation sequencing data for 311 individuals, retaining 4360 single‐nucleotide polymorphisms (SNPs) for population genomic analysis. Results We found that the two extant species are clearly delineated, corresponding well to current understanding of their respective distributions. The population genomic substructure in the brush‐tailed mulgara (211 samples, 2740 SNPs) aligns primarily with major drainage divisions. Inference of historical population size change indicated that all populations have likely had stable population sizes for much of the past 1000 years, although post‐European colonisation declines in some populations cannot be ruled out. The Pilbara population was most differentiated from other populations and displayed a stronger pattern of isolation‐by‐distance. Nevertheless, observed heterozygosity was similar across each of the populations ( H o = 0.078–0.090). Conclusions Stable population dynamics linked to the ecology of the mulgara and their high dispersal potential likely explain consistent levels of genetic diversity across most populations, but the effects of geography, such as major drainage divisions, drive the apparent contemporary population structure. Additional targeted tissue collection in under‐sampled regions is recommended to better quantify genomic diversity, structure, and genetic health across the species' full range.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Adapting to novel fire regimes: Using movement to inform conservation of a threatened arboreal mammal - Vivianna Miritis; Kita Ashman; Chris R. Dickman; Dale G. Nimmo; Tim S. Doherty (Biological Conservation, 2025)

Experimentally testing animal responses to prescribed fire size and severity - Tim S. Doherty; Daniel F. Bohórquez Fandiño; Darcy J. Watchorn; Sarah M. Legge; Chris R. Dickman (Conservation Biology, 2024)
Deserts are often highly biodiverse and provide important habitats for many threatened species. Fire is a dominant disturbance in deserts, and prescribed burning is increasingly being used by conservation managers and Indigenous peoples to mitigate the damaging effects of climate change, invasive plants, and land‐use change. The size, severity, and patchiness of fires can affect how animals respond to fire. However, there are almost no studies examining such burn characteristics in desert environments, which precludes the use of such information in conservation planning. Using a before‐after control‐impact approach with 20 sampling sites, we studied the outcomes of 10 prescribed burns of varying size (5–267 ha), severity, and patchiness to identify which variables best predicted changes in small mammal and reptile species richness and abundance. Three of the 13 species showed a clear response to fire. Captures increased for 2 species (1 mammal, 1 reptile) and decreased for 1 species (a reptile) as the proportional area burned around traps increased. Two other mammal species showed weaker positive responses to fire. Total burn size and burn patchiness were not influential predictors for any species. Changes in capture rates occurred only at sites with the largest and most severe burns. No fire‐related changes in capture rates were observed where fires were small and very patchy. Our results suggest that there may be thresholds of fire size or fire severity that trigger responses to fire, which has consequences for management programs underpinned by the patch mosaic burning paradigm. The prescribed burns we studied, which are typical in scale and intensity across many desert regions, facilitated the presence of some taxa and are unlikely to have widespread or persistent negative impacts on small mammal or reptile communities in this ecosystem provided that long unburned habitat harboring threatened species is protected.

Artificial refuges provide post-fire habitat for small vertebrates - Darcy J. Watchorn; Chris R. Dickman; Aaron Greenville; Barbara A. Wilson; Mark J. Garkaklis; Don A. Driscoll; Pat Hodgens; Dayna Hoadley; Heidi Groffen; Tim S. Doherty (Biological Conservation, 2024)

Meta‐analysis reveals impacts of disturbance on reptile and amphibian body condition - Kristina J. Macdonald; Don A. Driscoll; Kimberley J. Macdonald; Bronwyn Hradsky; Tim S. Doherty (Global Change Biology, 2023)
Ecosystem disturbance is increasing in extent, severity and frequency across the globe. To date, research has largely focussed on the impacts of disturbance on animal population size, extinction risk and species richness. However, individual responses, such as changes in body condition, can act as more sensitive metrics and may provide early warning signs of reduced fitness and population declines. We conducted the first global systematic review and meta‐analysis investigating the impacts of ecosystem disturbance on reptile and amphibian body condition. We collated 384 effect sizes representing 137 species from 133 studies. We tested how disturbance type, species traits, biome and taxon moderate the impacts of disturbance on body condition. We found an overall negative effect of disturbance on herpetofauna body condition (Hedges' g = −0.37, 95% CI: −0.57, −0.18). Disturbance type was an influential predictor of body condition response and all disturbance types had a negative mean effect. Drought, invasive species and agriculture had the largest effects. The impact of disturbance varied in strength and direction across biomes, with the largest negative effects found within Mediterranean and temperate biomes. In contrast, taxon, body size, habitat specialisation and conservation status were not influential predictors of disturbance effects. Our findings reveal the widespread effects of disturbance on herpetofauna body condition and highlight the potential role of individual‐level response metrics in enhancing wildlife monitoring. The use of individual response metrics alongside population and community metrics would deepen our understanding of disturbance impacts by revealing both early impacts and chronic effects within affected populations. This could enable early and more informed conservation management.

Identifying historical and future global change drivers that place species recovery at risk - William L. Geary; Ayesha I. T. Tulloch; Euan G. Ritchie; Tim S. Doherty; Dale G. Nimmo; Marika A. Maxwell; Adrian F. Wayne (Global Change Biology, 2023)
Ecosystem management in the face of global change requires understanding how co‐occurring threats affect species and communities. Such an understanding allows for effective management strategies to be identified and implemented. An important component of this is differentiating between factors that are within (e.g. invasive predators) or outside (e.g. drought, large wildfires) of a local manager's control. In the global biodiversity hotspot of south‐western Australia, small‐ and medium‐sized mammal species are severely affected by anthropogenic threats and environmental disturbances, including invasive predators, fire, and declining rainfall. However, the relative importance of different drivers has not been quantified. We used data from a long‐term monitoring program to fit Bayesian state‐space models that estimated spatial and temporal changes in the relative abundance of four threatened mammal species: the woylie ( Bettongia penicillata ), chuditch ( Dasyurus geoffroii ), koomal ( Trichosurus vulpecula ) and quenda ( Isoodon fusciventor ). We then use Bayesian structural equation modelling to identify the direct and indirect drivers of population changes, and scenario analysis to forecast population responses to future environmental change. We found that habitat loss or conversion and reduced primary productivity (caused by rainfall declines) had greater effects on species' spatial and temporal population change than the range of fire and invasive predator (the red fox Vulpes vulpes ) management actions observed in the study area. Scenario analysis revealed that a greater extent of severe fire and further rainfall declines predicted under climate change, operating in concert are likely to further reduce the abundance of these species, but may be mitigated partially by invasive predator control. Considering both historical and future drivers of population change is necessary to identify the factors that risk species recovery. Given that both anthropogenic pressures and environmental disturbances can undermine conservation efforts, managers must consider how the relative benefit of conservation actions will be shaped by ongoing global change.

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Animal mortality during fire - Chris J. Jolly; Chris R. Dickman; Tim S. Doherty; Lily M. van Eeden; William L. Geary; Sarah M. Legge; John C. Z. Woinarski; Dale G. Nimmo (Global Change Biology, 2022)
Earth's rapidly warming climate is propelling us towards an increasingly fire‐prone future. Currently, knowledge of the extent and characteristics of animal mortality rates during fire remains rudimentary, hindering our ability to predict how animal populations may be impacted in the future. To address this knowledge gap, we conducted a global systematic review of the direct effects of fire on animal mortality rates, based on studies that unequivocally determined the fate of animals during fire. From 31 studies spanning 1984–2020, we extracted data on the direct impacts of fire on the mortality of 31 species from 23 families. From these studies, there were 43 instances where direct effects were measured by reporting animal survival from pre‐ to post‐fire. Most studies were conducted in North America (52%) and Oceania (42%), focused largely on mammals (53%) and reptiles (30%), and reported mostly on animal survival in planned (82%) and/or low severity (70%) fires. We found no studies from Asia, Europe or South America. Although there were insufficient data to conduct a formal meta‐analysis, we tested the effect of fire type, fire severity, fire regime, animal body mass, ecological attributes and class on survival. Only fire severity affected animal mortality, with a higher proportion of animals being killed by high than low severity fires. Recent catastrophic fires across the globe have drawn attention to the plight of animals exposed to wildfire. Yet, our systematic review suggests that a relatively low proportion of animals (mean predicted mortality [95% CI] = 3% [1%–9%]) are killed during fire. However, our review also underscores how little we currently know about the direct effects of fire on animal mortality, and highlights the critical need to understand the effects of high severity fire on animal populations.

Abundance, Condition and Size of a Foundation Species Vary with Altered Soil Conditions, Remnant Type and Potential Competitors - Kristian Bell; Don A. Driscoll; John Patykowski; Tim S. Doherty (Ecosystems, 2021)

Reptile responses to anthropogenic habitat modification: A global meta‐analysis - Tim S. Doherty; Sara Balouch; Kristian Bell; Thomas J. Burns; Anat Feldman; Charles Fist; Timothy F. Garvey; Tim S. Jessop; Shai Meiri; Don A. Driscoll (Global Ecology and Biogeography, 2020)
Aim The aim was to determine how reptile populations respond to anthropogenic habitat modification and determine whether species traits and environmental factors influence such responses. Location Global. Time period 1981–2018. Major taxa studied Squamata. Methods We compiled a database of 56 studies reporting how habitat modification affects reptile abundance and calculated standardized mean differences in abundance (Hedges’ g ). We used Bayesian meta‐analytical models to test whether responses to habitat modification depended on body size, clutch size, reproductive mode, habitat specialization, range size, disturbance type, vegetation type, temperature and precipitation. Results Based on 815 effect sizes from 376 species, we found an overall negative effect of habitat modification on reptile abundance (mean Hedges’ g = −0.43, 95% credible intervals = −0.61 to −0.26). Reptile abundance was, on average, one‐third lower in modified compared with unmodified habitats. Small range sizes and small clutch sizes were associated with more negative responses to habitat modification, although the responses were weak and the credible intervals overlapped zero. We detected no effects of body size, habitat specialization, reproductive mode (egg‐laying or live‐bearing), temperature or precipitation. Some families exhibited more negative responses than others, although overall there was no phylogenetic signal in the data. Mining had the most negative impacts on reptile abundance, followed by agriculture, grazing, plantations and patch size reduction, whereas the mean effect of logging was neutral. Main conclusions Habitat modification is a key cause of reptile population declines, although there is variability in responses both within and between species, families and vegetation types. The effect of disturbance type appeared to be related to the intensity of habitat modification. Ongoing development of environmentally sustainable practices that ameliorate anthropogenic impacts is urgently needed to prevent declines in reptile populations.

A critique of 'countryside biogeography' as a guide to research in human‐dominated landscapes - Don A. Driscoll; Sara Balouch; Thomas J. Burns; Tim F. Garvey; Tricia Wevill; Kaori Yokochi; Tim S. Doherty (Journal of Biogeography, 2019)
Proliferation of redundant terms in ecology and conservation slows progress and creates confusion. ‘Countryside biogeography’ has been promoted as a new framework for conservation in production landscapes, so may offer a replacement for other concepts used by landscape ecologists. We conducted a systematic review to assess whether the 'countryside biogeography' concept provides a distinctive framing for conservation in human‐dominated landscapes relative to existing concepts. We reviewed 147 papers referring to countryside biogeography and 81 papers that did not. These papers were divided into categories representing three levels of use of countryside biogeography concepts (strong, weak, cited only) and two categories that did not use countryside biogeography at all but used similar concepts including fragmentation and matrix. We revealed few distinctions among groups of papers. Countryside biogeography papers made more frequent use of the terms 'ecosystem services', 'intensification' and 'land sparing' compared with non‐countryside biogeography papers. Papers that did not refer to countryside biogeography sampled production areas (e.g. farms) less often, and this related to their focus on habitat specialist species for which patch‐matrix assumptions were reasonable. Countryside biogeography offers a conceptual wrapper rather than a distinctive framework for advancing research in human‐modified landscapes. This and similar wrappers such as ‘conservation biogeography’ and ‘agricultural biogeography’ risk creating confusion among new researchers, and can prevent clear communication about research. To improve communication, we recommend using the suite of well‐established terms already applied to conservation in human‐modified landscapes rather than through an interceding conceptual wrapper.

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Ecosystem Responses to Fire: Identifying Cross-taxa Contrasts and Complementarities to Inform Management Strategies - Tim S. Doherty; Eddie J. B. van Etten; Robert A. Davis; Chris Knuckey; James Q. Radford; Sarah A. Dalgleish (Ecosystems, 2017)

Conserving long unburnt vegetation is important for bird species, guilds and diversity - Robert A. Davis; Tim S. Doherty; Eddie J.B. van Etten; James Q. Radford; Floyd Holmes; Chris Knuckey; Belinda J. Davis (Biodiversity and Conservation, 2016)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.